ESENSI LAPORAN NERACA KEUANGAN DALAM PENGAMBILAN KEPUTUSAN ORGANISASI RUMAH SAKIT - sri wahyuni; Budi Hartono; Anggy Vidian; Nurfarahin Nurfarahin (Jurnal Keperawatan Abdurrab, 2025)
The balance sheet plays a crucial role in the strategic decision-making of hospitals by assessing financial health and operational sustainability. This article explores how the main elements of the balance sheet working capital, operating costs, cash flow, and capital structure can significantly impact managerial effectiveness and hospital profitability. Optimal management of working capital, for instance, can improve cost efficiency by ensuring that the hospital has sufficient funds for operational needs without compromising financial stability. On the other hand, analyzing operating costs is essential, especially in crisis situations like a pandemic, when hospitals face greater cost challenges. Cash flow becomes a key element for maintaining liquidity, ensuring that the hospital can meet its financial obligations on time and avoid liquidity issues that could disrupt daily operations. Additionally, a balanced capital structure helps support the financial stability of the hospital, minimizes risks, and strengthens its ability to invest in improving health services and facilities. A thorough understanding of each component of the balance sheet forms the foundation for strategic and efficient decision-making, ultimately focusing on growth, sustainability, and the enhancement of healthcare quality.